2021
DOI: 10.1016/j.socscimed.2021.113773
|View full text |Cite
|
Sign up to set email alerts
|

Geographic access to COVID-19 healthcare in Brazil using a balanced float catchment area approach

Abstract: The rapid spread of COVID-19 across the world has raised concerns about the responsiveness of cities and healthcare systems during pandemics. Recent studies try to model how the number of COVID-19 infections will likely grow and impact the demand for hospitalization services at national and regional levels. However, less attention has been paid to the geographic access to COVID-19 healthcare services and to hospitals’ response capacity at the local level, particularly in urban areas in the Global South. This p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 38 publications
3
44
0
1
Order By: Relevance
“…This should be considered when planning hospitals and health centres in rapidly growing developing countries, since an unequal distribution of hospitals with a concentration in the central metropolitan areas is currently common [ 26 ]. Consistent with the findings of Pereira et al [ 32 ] in Brazil, our study found that there is an intense spatial inequality between downtown areas and marginal poor neighbourhoods with respect to access to PHs and PVCs. Our findings also suggest that a significant number of CTs around the city had virtually no access to COVID-19 vaccinations due to the dearth of hospitals there.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This should be considered when planning hospitals and health centres in rapidly growing developing countries, since an unequal distribution of hospitals with a concentration in the central metropolitan areas is currently common [ 26 ]. Consistent with the findings of Pereira et al [ 32 ] in Brazil, our study found that there is an intense spatial inequality between downtown areas and marginal poor neighbourhoods with respect to access to PHs and PVCs. Our findings also suggest that a significant number of CTs around the city had virtually no access to COVID-19 vaccinations due to the dearth of hospitals there.…”
Section: Discussionsupporting
confidence: 92%
“…A study in Brazil measured the geographic access to COVID-19 healthcare services using a balanced float CA approach and identified substantial social and spatial inequalities in access to health services during the pandemic [ 32 ]. Their findings indicated that ICU equipment availability varied considerably between cities and was substantially lower among Black communities and those of the poor [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, previous studies have found that access to COVID-19 health services tends to be lower in less developed regions in the country, 41 42 particularly among low-income and black communities. 43 Only 25% of Brazilians have access to private healthcare via health insurance, reflecting how inequality in access to quality healthcare is largely driven by income. 44 This leaves 75% of the population solely reliant on a chronically underfunded public healthcare system, which highlights a double disadvantage for low-income and non-White populations, who are more likely to be infected and deprived of care.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, one practical limitation can be the lack of access to spatially-explicit health data like, for instance, the geographic origin of hospitalised patients. To circumvent this issue, we here propose an analytical framework based on the definition of hospital catchment areas (HCAs), a concept that has previously been used to study the geographic access to healthcares in the context of the COVID-19 epidemic in Brazil [ 5 ]. The overall objective of our study is to present and describe an analytical framework based on the delimitation of such HCA units and that allows to analyse the dynamic of potential drivers of COVID-19 hospitalisation incidence in a spatially-explicit context.…”
Section: Introductionmentioning
confidence: 99%